Ta’tsῑru fahmi al nusūs al maqrū’ah bithorῑqoti al tahdhῑru fῑ tarqiyyati mahāroh al qirō’ah ladā al thullābu al jālisῑna fῑ al soffi al tsālitsi al ‘āli bima’had dāru al lughah wa al da’wah - Solehudin, Muhamad; Zaki Abouelnasr (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
Dar Al-Lughah and Da’wah Institute in Banqil was very interested in the skill of its students in reading ancient heritage books while taking into account the grammatical and morphological rules. They were trained in applying what they had received from their sheikh’s reading and were distinguished by their understanding of the grammatical and morphological rules and applying them in their reading with grammatical symbols word by word, but they were far from Proficiency in reading the Arabic language even though they have focused their thoughts and minds on achieving that proficiency in speech and writing. Therefore, the aim of this research is to describe the effect of understanding the texts read through the preparation method in improving the reading skill of students sitting in the third higher semester at the Dar Al-Lughah and Da’wah Institute in Bangalore, East Java. The approach to this research is quantitative, and its type is experimental, because this research attempts to take the influence of certain variables on others, such as an attempt to improve reading skill through preparation in understanding read texts. The data collection method used in this research: observation, interview, questionnaire, and test. The results of this research are that H0 is accepted and H1 is rejected because there is no difference in the +- mean between the pre-test and post-test for the two groups. Therefore, there is no difference in the average value of the posttest between the two groups, so that it can be said that the method of preparation has no effect on improving reading skill.